2013
DOI: 10.3390/coatings3010026
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Convective-Sedimentation Assembly of Colloidal Microsphere Coatings for Biotechnology Applications

Abstract: Continuous convective-sedimentation assembly (CCSA) is a deposition method that constantly supplies the coating suspension to the meniscus behind the coating knife by inline injection, allowing for steady-state deposition of ordered colloids (which may include particles or cells or live cell-particle blends) by water evaporation. The constant inflow of suspended particles available for transport to the drying front yields colloidal arrays with significantly larger surface areas than previously described and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…This is consistent with the results of Fig. 2 discussed earlier. In this context, the possibilities of latex coatings to develop high surface-to-volume ratio surfaces by different deposition methods capable of generating very thin coatings with high cell densities is starting to be explored (Fidaleo et al, 2014;Jenkins et al, 2013).…”
Section: Toluene Biodegradation In Non-wetted Bioactive Latex Coatingsmentioning
confidence: 99%
“…This is consistent with the results of Fig. 2 discussed earlier. In this context, the possibilities of latex coatings to develop high surface-to-volume ratio surfaces by different deposition methods capable of generating very thin coatings with high cell densities is starting to be explored (Fidaleo et al, 2014;Jenkins et al, 2013).…”
Section: Toluene Biodegradation In Non-wetted Bioactive Latex Coatingsmentioning
confidence: 99%
“…Some common biocoating deposition techniques include extrusion [34,90,91], spray drying [92], the wire wound rod drawdown Mayer rod coating method [13,67,93], 3-D ink-jet deposition [94] and the convective assembly [12,47,95]. Recently, dielectrophoresis (DEP) has also been used to generate photoreactive cyanobacteria cell monolayers on top of polyelectrolyte adhesives [96].…”
Section: Preparation Of Biocoatingsmentioning
confidence: 99%
“…Kumnorkaew et al [97] demonstrated that when the meniscus height is larger than the particle diameter, multilayer coatings will form [97]. The number and type of layers is easily adjusted by altering the suspension volume fraction and coating knife speed, allowing for precise control in particle packing and coating thickness [95,97,98] (Fig. 2B).…”
Section: Preparation Of Biocoatingsmentioning
confidence: 99%
“…Further optimization of the latex coating emulsion and ink-jet printing system (not the focus of this work) will allow for the generation of significantly more surface area and an increased number of reactive cells per coating microstructure. Improvements in surface area as a function of aspect ratio can be seen in Table 2, where ink-jet coatings are compared with a monolayer of G. oxydans cells, as could be obtained by convective-sedimentation assembly [50]. Increased available surface area can come through improving ink-jet methods (ink formulation, droplet control).…”
Section: Generation Of Increased Surface Area Biocoatings Using Ink Jmentioning
confidence: 99%